Involuntary Resettlement - The Inspection Panel (The Inspection Panel, Washington, DC, 2016)
This report on involuntary resettlement is the first in a series of papers to be published by The World’s Bank Inspection Panel with the aim of drawing on the main emerging lessons from its caseload over 22 years. The Panel hopes the lessons presented in this study can highlight areas in which continued improvements can enhance the Bank’s overall approach to resettlement and, in that regard, be useful to both the Bank and the global development community. The Inspection Panel was created in 1994 by the World Bank’s Board of Directors to receive complaints submitted by people suffering harm allegedly caused by Bank projects. Since then, the Panel has received 105 Requests for Inspection. Of those, 85 have been registered and 32 investigated. Two additional investigations are underway.